Influence of BMI Value and the Percentage of Fat Tissue on the Curvature of the Foot Longitudinal Arch among Students of University of Physical Education in Kraków - Przemysław Madejski; Aneta Bac; Roger Madejski (University of Applied Sciences in Tarnow, Poland, 2018)
Introduction: The foot is an essential element of the kinetic system. Performing the supporting function, it maintains the correct body posture, but above all it is used while walking. Feet are vulnerable to all the changes that occur in human environment. The civilisation changes are particularly harmful to the locomotor system. Material and methods: The research was conducted in the academic year 2014/2015 among the second year Physiotherapy and Physical Education students in the University of Physical Education in Kraków. The total of 93 students took part in the research (48 females and 45 males). The average age of the subjects was 21 years. In order to assess the curvature of the foot longitudinal arch a podoscope was used, whereas the Tanita BC-418 scales were applied to define the BMI value and calculate the percentage of body fat tissue. Results: A vast majority of the subjects (70.9%) had a normal type of foot longitudinal arch. Higher longitudinal arch occurred more frequently among women than men, the normal type was less frequent. The BMI level was also within the norm among the majority of the students (79.6%). Overweight was more frequent among males than females. Both males and females with the correct BMI value in their majority had normal curvatures of both feet longitudinal arches. The highest percentage (75%) of the regular right foot longitudinal arch was recorded among females with low body fat deposition. In the case of the left foot the percentage was 68.8%. All the males with low fat deposition obtained normal values of the longitudinal arch curvature for both feet. Conclusions: The subjects most frequently had a regular curvature of foot longitudinal arch. No significant influence of the percentage of fat tissue and BMI value on the Clarke's angle was recorded.